Prospek Penerapan Traceability Perikanan Udang Di Pelabuhan Perikanan Samudera Cilacap (Implementation Prospects For Traceability of Shrimp Fisheries In Cilacap Oceanic Fishing Port) - Budy Wiryawan; Risah Palevi; Prihatin Ika Wahyuningrum (Jurnal Perikanan dan Kelautan, 2021)
Cilacap is one of the shrimp exporter areas in Indonesia. The exported shrimp from this area is mostly dominated by aquaculture and capture fisheries. The prospect of shrimp catch traceability has not been applied because it is still complicated in term of information about the fishing ground of shrimp and shrimp catch data from supplier and lack of governance. Shrimp fisheries in Cilacap are dominated by small-scale fisheries that usually have not been certified and may be affected by international commerce. Based on that explanation, it is important to conduct a study about shrimp traceability readiness in Cilacap. A purposive sampling and accidental sampling method were used in this research, accompanied by descriptive content analysis. The result shows that the readiness of Cilacap shrimp fisheries is still in the stage of concept preparation. The standard value of handling and processing shrimp according to Indonesian National Standard. Facilities that support the traceability system function properly. Enumeration intervention may be used to support a proper small-scale fisheries traceability in Cilacap.